2022
DOI: 10.1210/clinem/dgac561
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dysregulation in Adult Survivors of Pediatric Hematopoietic Stem Cell Transplantation: The Role of Incretins

Abstract: Context Survivors of pediatric hematopoietic stem cell transplantation (HSCT) have increased risk of developing metabolic syndrome (MetS), but the mechanisms are poorly understood. Objective To test the hypothesis that insufficient secretion of glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) plays a pathogenetic role in HSCT survivors with MetS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 55 publications
2
3
0
Order By: Relevance
“…Despite previous treatment with cytotoxic regimen pre‐HSCT, previous acute GvHD and the use of parenteral nutrition, found to have detrimental effects on the gastrointestinal epithelial cells, 37,38 we found a preserved gut‐bone axis with a normal postprandial suppression of CTX in these survivors. This finding is supported by a recent study from our group, where a normal incretin hormone response in long‐term survivors of pediatric HSCT was observed 3 …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Despite previous treatment with cytotoxic regimen pre‐HSCT, previous acute GvHD and the use of parenteral nutrition, found to have detrimental effects on the gastrointestinal epithelial cells, 37,38 we found a preserved gut‐bone axis with a normal postprandial suppression of CTX in these survivors. This finding is supported by a recent study from our group, where a normal incretin hormone response in long‐term survivors of pediatric HSCT was observed 3 …”
Section: Discussionsupporting
confidence: 88%
“…bone axis with a normal postprandial suppression of CTX in these survivors. This finding is supported by a recent study from our group, where a normal incretin hormone response in long-term survivors of pediatric HSCT was observed 3. Other possible treatments for osteopenia are available including calcium and vitamin D replacement therapy and treatment with bisphosphonates.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Moreover, a reduced pancreatic volume has been found after a radiation-based conditioning regimen, suggesting that RT has a direct role in the onset of insulin resistance and diabetes after HSCT [ 59 ]. Recently, a cross-sectional cohort study demonstrated an altered production of incretin hormones in HSCT survivors previously treated with TBI, with them developing dyslipidemia and abdominal adiposity [ 60 ].…”
Section: Tbi-associated Late Toxicitiesmentioning
confidence: 99%